Strategies for Developing the Quality of SMK Education Islamic High School Majoring in Multimedia and Technology Information (Case Study in Parung Panjang District - Bogor Regency) - Syahlarriyadi, Syahlarriyadi; Sulaiman, Suhendar; Zulfitria, Zulfitria (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study uses a qualitative method with the Analytical Hierarchy Process (AHP) to analyze the strategy for developing the quality of Islamic vocational school education majoring in multimedia and information technology in the Parung Panjang area, Bogor Regency, with a focus on school accreditation, human resources, curriculum, and infrastructure. In addition, this study develops alternative quality development strategies that can be applied not only in the region but also in general throughout Indonesia. The results of this research show that the main criteria for developing quality of education at Islamic Vocational Schools consisted of managerial (A1, A2), curriculum (A2, A3), human resource (A3, A4), infrastructure (A4, A5), and human resources (A4). The findings of this study can be used as a reference for the implementation of strategies in Islamic vocational schools, and cultivating strategies that have a positive impact on Islamic education both at the national and international levels.